CEO Overconfidence dan CEO Power terhadap Sustainability Performance: Peran Moderasi Dewan Independen - Mariska Ramadana; Serena Phang; Ria Karina (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study looks at how CEO overconfidence and power impact business sustainability performance while taking the independent board's moderating function into account. Methodology: Using multiple regression approaches, the study method examines the association between the variables by analyzing secondary data from public businesses listed on the Indonesia Stock Exchange (IDX) and sustainability reports released between 2018 and 2022. Results: The analysis's findings demonstrate that CEO power and overconfidence significantly impact corporate sustainability performance, and that an independent board's function cannot mitigate this relationship. This could imply that although independent boards serve as checks and balances, they might not have as much authority to affect or counteract choices made by a CEO who is extremely self-assured and influential. Conclusions: The individual attributes of a CEO, such as overconfidence and power, play a significant role in determining a company's sustainability performance. Limitations: This study faces several limitations, including reliance on secondary data sourced from the company's annual reports, a restricted range of analyzed variables, and the application of multiple linear regression analysis, which may not fully account for the intricate relationships between variables. Contributions: This research contributes to the advancement of corporate governance theory and practice in the context of sustainability.